Epidemiological changes with potential implication for antifungal prescription recommendations for fungaemia: data from a nationwide fungaemia surveillance programme. (22nd April 2013) - Arendrup, M. C.; Dzajic, E.; Jensen, R. H.; Johansen, H. K.; Kjældgaard, P.; Knudsen, J. D.; Kristensen, L.; Leitz, C.; Lemming, L. E.; Nielsen, L.; Olesen, B.; Rosenvinge, F. S.; et al.
Abstract: Significant changes in the management of fungaemia have occurred over the last decade with increased use of fluconazole prophylaxis, of empirical treatment and of echinocandins as first‐line agents for documented disease. These changes may impact the epidemiology of fungaemia. We present nationwide data for Denmark from 2010 to 2011. A total of 1081 isolates from 1047 episodes were recorded in 995 patients. The numbers of patients, episodes and recovered isolates increased by 13.1%, 14.5% and 14.1%, respectively, from 2010 to 2011. The incidence rate was significantly higher in 2011 (10.05/100 000) than in 2010 (8.82/100 000), but remained constant in the age groups 0–79 years. The incidence rate was highest at the extremes of age and in males. Candida albicans accounted for 52.1% but declined during 2004–11 (p 0.0155). Candida glabrata accounted for 28% and increased during 2004–2011 (p <0.0001). Candida krusei, Candida tropicalis and Candida parapsilosis remained rare (3.3–4.2%). The species distribution changed with increasing age (fewer C. parapsilosis and more C . glabrata ) and by study centre. Overall, the susceptibility rates were: amphotericin B 97.3%, anidulafungin 93.8%, fluconazole 66.7%, itraconazole 69.6%, posaconazole 64.2% and voriconazole 85.0%. Acquired echinocandin resistance was molecularly confirmed in three isolates. The use of systemic antifungals doubled over the last decade (2002–2011) (from 717 000 to 1 450 000 defined daily doses/year) of which the vast majority (96.9%) were azoles. The incidence of fungaemia continues to increase in Denmark and is associated with a decreasing proportion being susceptible to fluconazole. Changes in demography, higher incidence in the elderly and higher antifungal consumption can at least in part explain the changes.